Advanced control of OLTC-enabled LV networks with PV systems and EVs - Franco, John Fredy [UNESP]; Procopiou, Andreas T.; Quirós-Tortós, Jairo; Ochoa, Luis F. (Institution of Engineering and Technology (IET), 2019)
The simultaneous uptake of residential photovoltaic (PV) systems and electric vehicles (EVs) can lead to contrasting voltage problems (i.e. voltage rise and drop) in low-voltage (LV) networks throughout the day. While solutions that directly manage these technologies can be effective in mitigating their impacts, they affect or require interactions with customers. A more practical alternative for distribution network operators (DNOs) is, therefore, to manage voltages using only network assets. For this purpose, two advanced methods to control on-load tap changer fitted transformers, owned and operated by DNOs, are proposed: a rule-based control method that only requires monitoring from remote points and a three-phase optimal power flow-based control method that requires full observability and adopts a simple – yet effective – forecasting to cater for future uncertainties. The performance of the proposed methods is thoroughly assessed within a stochastic approach on a real UK LV network considering realistic 1 min resolution demand, PV, and EV profiles. Results show that both methods are effective in managing contrasting voltage problems caused by both PV systems and EVs. While the optimisation method leads to the lowest number of tap changes, the rule-based method, given its limited observability requirement, could be considered a practical interim solution.